Documentary Method–Reflecting Possibilities of a Qualitative-Reconstructive Research Method for Examining Value-Oriented Learning in the Geography Classroom - Applis, Stefan (Journal of Geography Education, 2013)
The presented research project wants to contribute to the reflection of possibilities of value-oriented learning in the geography classroom and to its evaluation within the framework of qualitative-reconstructive research. In this context a new research method (documentary method) that is complex enough to cover the field of value-oriented learning in an evaluative way is introduced to geography education. This means incorporating explicit value-based judgments as well as implicit value-based orientations – a distinction which other qualitative approaches, e.g. qualitative content analysis, do not accomplish.